Distribution and molecular characterization of Squash mosaic virus on cucumber in Gianyar, Bali - Listihani Listihani; Ni Putu Pandawani; Tri Asmira Damayanti; Mimi Sutrawati; Dewa Gede Wiryangga Selangga; Ketut Ayu Yuliadhi; Trisna Agung Phabiola; Gusti Ngurah Alit Susanta Wirya (Universitas Lampung, 2022)
Squash mosaic virus (SqMV) has been reported to infect cucumber plants in Java and cause a decrease in fruit quality and quantity. Until now, there is no information regarding Sqmv infection in Cucurbitaceae in Bali. In a preliminary research conducted during 2020, we found mosaic symptoms in Gianyar, Bali. SqMV was inferred to be the possible cause of the virus-disease-like symptoms. The study aimed to determine the precence of SqMV in Gianyar, Bali and to obtain information related to its molecular character. This research method includes surveys, field observations, virus identification by RT-PCR, and DNA analysis. Severe disease incidence caused by SqMV was observed on cucumber cultivation in Gianyar that was in the range of 5.81–66.87%. PCR using specific primer for coat protein (CP) gene of SqMV was successfully amplified the DNA fragments of ± 582 bp on samples from Payangan, Tegallalang, Ubud, Sukawati, Blahbatuh, and Gianyar districts, except for samples from Tampaksiring. This indicates that the presence of SqMV is widespread in Java and Gianyar.The SqMV isolate from Bali had the highest nucleotide homology at 91.9–93.4% and amino acids 94.0–94.5 and was closely related to the Brazil isolate (KT923125) and had lower isolate homology than other countries (China, Trinidad, Spain, Japan, Arizona, Cekoslowakia, and Australia). It proved that those mosaic symptoms on cucumber is associated with SqMV infection. SqMV is classified as a quarantine organism of category A2, so it is necessary to prevent its spread to other areas.